Fantastic beasts and where to find them [videorecording (DVD)] - Rowling, J. K.; Redmayne, Eddie, 1982-; Waterston, Katherine; Fine Frenzy, 1984-; Depp, Johnny (Warner Home Video, 2017)
It opens in 1926 as Newt Scamander has just completed a global excursion to find and document an extraordinary array of magical creatures. Arriving in New York for a brief stopover, he might have come and gone without incident, were it not for a No-Maj (American for Muggle) named Jacob, a misplaced magical case, and the escape of some of Newt's fantastic beasts, which could spell trouble for both the wizarding and No-Maj worlds.